Panel Data Analysis: Supply Chain Strategy Effects on Capital Structure of Companies Listed in the Jakarta Islamic Index - Wuryaningsih Dwi Lestari; Ma’ruf Ma’ruf; Wafiatun Mukharomah; Anestia Retno Kusumastuti; Muhammad Sholahuddin (International Journal of Supply Chain Management, 2020)
Abstract— The purpose of this research is to analyze the influence of supply chain process, firm size, supply chain strategy, profitability, tangibility, and growth opportunity variables, Leverage, Volatility, Retained Earnings, Non Debt Tax Shield, and Free Cash Flow on capital structure of companies listed in the Jakarta Islamic Index (JII). This research is a development of thesis research ever conducted by researchers by adding independent variables and analysis techniques using panel data analysis. This study uses secondary data in the form of financial statements from each company. The sampling uses purposive sampling. The population in this study is companies listed in JII for the period 2008-2018 with a sample of four companies because there are only four companies that have been listed in JII since 2008 and have complete financial statements in that year. To analyze several variables that affect the capital structure, panel data analysis techniques are used. The results showed that firm size, supply chain strategy, tangibility, growth opportunity, leverage, volatility, retained earnings, non-debt tax shield, and free cash flow simultaneously affect the profitability. The results of this study can be used as an indication, which factors must be remembered by choosing the optimal capital structure for the company through the supply chain strategy.